An Examination of the Determinants of the Adoption of Mobile Applications as Learning Tools for Higher Education Students - Chuchu, Tinashe; Ndoro, Tinashe (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The main purpose of the present study was to examine whether mobile applica-tions could be adopted as feasible tools for learning purposes at higher education institutions. Furthermore the study’s intention was to conduct an empirical inves-tigation into students’ perceptions towards mobile applications being introduced as learning aids. The researcher developed a conceptual model derived from the technology acceptance model in order to measure the constructs used in the study. Adopting a quantitative approach, the field study was conducted in South Africa at a selected higher education institution. Research data was collected from 380 registered students at the selected higher education institution who were older than 18 years. Using SPSS 23 and AMOS 23 software programs, Structural Equation Modeling (SEM) was performed to analyse the data set. The results re-vealed that perceived usefulness, perceived ease of use, attitudes towards a mo-bile application, intention to use a mobile application were all significant predic-tors for the actual use of mobile applications for learning. The findings of the study illuminate the importance of the determinants of the adoption of mobile ap-plications for learning in higher education.